Hubungan Glasgow Coma Scale (GCS) dan Kadar Trombosit dengan Lama Rawat Pasien Sepsis di RSU Cut Meutia Aceh Utara - Aida Fitri Harahap; Muhammad Sayuti; Meutia Maulina (MES Bogor, 2025)
Sepsis is a life-threatening organ malfunction caused by the dysregulation of the body's reaction to infection. Septic dysfunction can occur in almost any organ, which ends in multi-organ disfunction. Decreased thrombocyte levels and decreased awareness as parameters of organ dysfunction in sepsis can increase the risk of prolonged treatment. The aim of the research is to find out the relationship between GCS and thrombocyte levels with the long-term treatment of sepsis patients. Research with cross-sectional analytical observational methods, carried out at Cut Meutia North Aceh RSU, September - November 2023. The sample was 63 patients diagnosed with sepsis according to the inclusion and exclusion criteria obtained from medical records. The results of the study included 43 men (68.3%), 35 men (55.6%) with long-term treatment (>6 days), 32 people (50.8%) with normal thrombocyte levels (150,000-450,000/μl), and 51 people (81%) with GCS 15 or composmentis. Spearman's results showed no significant relationship between thrombocyte levels (p=0.846) and GCS (p =0.153) with the length of treatment of sepsis patients.